2021
DOI: 10.1111/jfpp.16120
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of microwave‐assisted extraction of anthocyanins in red cabbage by response surface methodology

Abstract: Response surface methodology was performed to optimize the microwave-assisted extraction of red cabbage anthocyanins. Influence of solid:solvent ratio (1:10, 1:20, and 1:30, w:w), extraction time (5, 10, and 15 min), and microwave power (200, 400, and 600 W) on total monomeric anthocyanin (TMA) content was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Several studies have shown that MAE has some advantages compared to conventional extraction [ 58 , 59 , 60 , 61 , 62 ]. These studies claim that MAE lasts for less time and consumes less solvent [ 58 ], and allows higher extraction yields than a conventional extraction [ 41 , 56 ]. In addition, it is an energy-saving method due to its short processing time.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that MAE has some advantages compared to conventional extraction [ 58 , 59 , 60 , 61 , 62 ]. These studies claim that MAE lasts for less time and consumes less solvent [ 58 ], and allows higher extraction yields than a conventional extraction [ 41 , 56 ]. In addition, it is an energy-saving method due to its short processing time.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
“…Despite the need to control and optimize the thermal conditions under which MAE is carried out to avoid a negative effect on the antioxidant properties and the color of the extract obtained, several studies have been carried out to explore the possible application of this technique in the extraction of anthocyanins [Table 2]. Several studies have shown that MAE has some advantages compared to conventional extraction [58][59][60][61][62]. These studies claim that MAE lasts for less time and consumes less solvent [58], and allows higher extraction yields than a conventional extraction [41,56].…”
Section: Microwave-assisted Extraction (Mae)mentioning
confidence: 99%
“…However, the sample matrix and solvent have more surface area in contact with one another, which boosts extraction yield. [ 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the optimal extraction process parameters were obtained as follows: extraction time of 4 min, microwave power of 200 W, extraction temperature of 40 °C, and solid-to-liquid ratio of 1:20 g/mL. The yield of anthocyanins was 241.20 mg/L under these parameters [ 30 ]. Anthocyanins from red bean seed coats were extracted via MAE, and the extraction process was optimized using RSM.…”
Section: Anthocyanin Extraction Methodsmentioning
confidence: 99%